Amaranther families of Tulyehualco, Mexico City: between the traditional and the modern - Ramírez Meza, Beatriz; Manzo-Ramos, Fernando; Pérez Olvera, Ma. Antonia; León Merino, Aurelio (Revista Mexicana de Ciencias Agrícolas, 2017)
Santiago Tulyehualco is a town in the rural area of  Mexico City, where amaranth families grow, transform  and market amaranth, and coexist between traditional  and modern. Through their practices in the different  productive phases, this coexistence manifests itself, from  which they have used their traditional knowledge to adapt,  innovate and create a diversity of products elaborated in  their family agro-industries, creating jobs and income  in their families and through time it has become a life  option and therefore a development option. The objective  of this paper was to demonstrate that for amaranther  families there is the coexistence of the traditional and  the modern, expressed through their activities. Field  data from three research projects (2004, 2011 and 2017)  conducted by Universidad Autónoma Chapingo and the  Colegio de Postgraduados, where 50 producers and 18  families were interviewed, semi-structured interviews,  bibliographic review and observation were used. The  information shown is analyzed and discussed from the  theoretical perspective of urban anthropology, proposed  by Bonfil-Batalla (1988), using holistic analysis and the  ethnographic method.
Keywords: family agribusiness, amaranth, traditional, modern